Impacto do Programa de Saúde da Família sobre indicadores de saúde bucal na população de Natal -RN - Patrício, Alberto Allan Rodrigues (2007)
The aim of this study was to assess the impact of the Family Health Program (FHP) on a number of oral health indicators in the population of Natal, Brazil. The study is characterized as a quasi-random community intervention trial. The intervention is represented by the implementation of an Oral Health Team (OHT) in the FHP prior to the study. A total of 15 sectors covered by the FHP with OHT were randomly drawn and paired with another 15 sectors, based on socioeconomic criteria, not covered by the teams. A few sectors were lost over the course of the study, resulting in a final number of 22 sectors, 11 covered and 11 not covered. We divided the non-covered areas into two conditions, one in which we considered areas that had some type of assistance program such as the Community Agents Program (CAP), FHP without OHT, BHU (Basic Health Unit) or no assistance, and the other, in which we considered areas that had only BHU or no assistance. Community Health Agents (CHAs) and Dental Office Assistants (DOAs) applied a questionnaire-interview to the most qualified individual of the household and the data obtained per household were transformed into the individual data of 7186 persons. The results show no statistical difference between the oral health outcomes analyzed in the areas covered by OHT in the FHP and in non-covered areas that have some type of assistance program, with a number of indicators showing better conditions in the non-covered areas. When we considered the association between covered and non-covered areas under the second condition, we found a statistical difference in the coverage indicators. Better conditions were found in covered areas for indicators such as I have not been to the dentist in the last year with p < 0.001 and OR of 1.64 and I had no access to dental care with p < 0.001 and OR of 2.22. However, the results show no impact of FHP with OHT on preventive action indicators under both non-covered conditions. This can be clearly seen when we analyze the toothache variable, which showed no significant difference between covered and non-covered areas. This variable is one of the most sensitive when assessing oral health programs, with p of 0.430 under condition 1 and p of 0.038 under condition 2, with CI = 0.70-0.90. In the analysis of health indicators in children where the proportion of deaths in children under age 1, the rate of hospitalization for ARI (Acute Respiratory Infections) in those under age 5 and the proportion of individuals born underweight were considered, a better condition was found in all the outcomes for areas with FHP. Therefore, we can conclude that oral health in the FHP has little effect on oral health indicators, even though the strategy improves the general health conditions of the population, as, for example child health